Essays on the relationship between municipal public policies and election cycle - Ferreira, Jorge Leandro Delconte (2016)
: This thesis consists in a set of three essays about elections and public spent in federative systems, linked with a central research problem: How elections affect the allocation of public revenues in local governments and in federations with various levels of government? One of the main questions of democratic politics concern the interactions between popular choices (expressed by voting) and public policy and federative systems usually propose decentralization and interdependence between different levels of government as an important mechanism for increasing efficiency, transparency and accountability. However, other authors have pointed out that, when it comes to incumbents' choices about allocation of public budget, there are much more elements to consider than solely the public welfare. We intent to cover additional issues to contribute in explaining where, how and why policymakers allocate public revenues in fiscal federations. We perform that in three interconnected essays, by using different (and complementary) methodological shapes, but always combining theoretical propositions and empirical evidences. In the first essay, we addressed political and electoral reasons in the allocation of intergovernmental transfers in a federative state. We performed a panel data analysis encompassing 2856 Brazilian municipalities from 1999 to 2011. Results suggest that deputies play an important role in the allocation of grants, as well as the alignment between local and central chief executives, and there is a negative correlation with opposition parties' mayors. Moreover, changes in alliance status between budget-voting year and budget-implementation year influence the amount of transfers. However, the main effect over the allocation of grants was the electoral calendar, encompassing both local and central elections. The second essay theoretically discuss the timing of elections and its effects in the allocation of short-term and long-term expenditures federative systems. Guided by the stylized fact that synchronized elections produce lower bias levels in the expenditures, we built a system equations' model and solve it to show that incumbents have stimuli to increase short-term expenditures in electoral years. We also discussed theoretical implications of this anticipation effect by contrasting local versus central elections and synchronized versus staggered elections. In the third essay, we demonstrate spatial correlations in public spent at local level, due to spillovers in provision of public goods in local and regional layers. We performed a spatial analysis in health expenditure at the local level in all 399 municipalities in the Paraná state, from 2005 to 2012. We find that the spatial effect has a significant role in explaining health expenditures in the local level, both in electoral and non-electoral years. Furthermore, the electoral calendar seems to change the intensity of the coefficients in some independent variables (e.g., population age) and even changes the direction in some variables' effects (as population density). Indeed, the negative effect of population density changes in positive, probably as a political strategy to seduce voters. Estimations suggest that health spent constitute an important tool to seduce voters, especially in local elections (which an effect almost twice stronger than central ones) and both central and local elections' years rise the local public budget allocation in health. Although we have strongly based our essays in previous studies, this thesis is more than an afterthought of Cox & McCubbins (1986) and Lindbeck & Weibull (1987) models. First, for the best of our knowledge, we are the first to add the issue of deputies' role in intergovernmental grants. Second, the comparison of electoral effects in synchronized and staggered elections and the addition of spatial effects when it comes to budget allocation is also an innovation in the literature. Previous scholars have issued this factors, but their approach differs because the focus is far from elections timing, and when they issue synchronized and staggered elections, the focus is not the budget allocation. These essays may be useful to additional investigations that aim to discuss political alignment and its influence in allocation of public resources, in order to enhance understanding and create or ameliorate mechanisms of regulation that improve efficiency in political processes and public spent.